Folate-receptor-targeted co-self-assembly carrier-free gemcitabine nanoparticles loading indocyanine green for chemo-photothermal therapy - Kuang, Shuang; Liu, Shuhan; Wang, Shiyu; Yang, Liang; Zeng, Yingchun; Ming, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
The carrier-free chemo-photothermal therapy has become a promising strategy to improve anti-cancer therapeutic efficacy owing to the combination of chemotherapy and photothermal therapy, with improved chemotherapy drug pharmacodynamics and pharmacokinetics, high drug loading, and reduced toxicity. We designed a novel carrier-free targeting nanoparticles, co-self-assembled amphiphilic prodrugs 3′,5′-dioleoyl gemcitabine (DOG), and tumor-targeted γ-octadecyl folate (MOFA), with encapsulated US Food and Drug Administration (FDA)-approved photosensitizer indocyanine green (ICG) for synergistic chemo-photothermal therapy. The DOG linking oleic acid to the sugar moiety of gemcitabine (GEM) showed better self-assembly ability among GEM amphiphilic prodrugs linking different fatty acids. The readily available and highly reproducible 3′,5′-dioleoyl gemcitabine/γ-octadecyl folate/indocyanine green (DOG/MOFA/ICG) nanoparticles were prepared by reprecipitation and showed nano-scale structure with mono-dispersity, great encapsulation efficiency of ICG (approximately 74%), acid- and laser irradiation-triggered GEM release in vitro and sustained GEM release in vivo after intravenous administration as well as excellent temperature conversion (57.0°C) with near-infrared laser irradiation. The combinational DOG/MOFA/ICG nanoparticles with near-infrared laser irradiation showed better anti-tumor efficacy than individual chemotherapy or photothermal therapy, with very low hemolysis and inappreciable toxicity for L929 cells. This co-self-assembly of the ICG and the chemotherapy drug (GEM) provides a novel tactic for the rational design of multifunctional nanosystems for targeting drug delivery and theranostics.